Donation Collection Method: Nudging to Minimize Cost Aversion - Balqiah, T. Ezni; Kusumawardhani, Dianti E (ASEAN Marketing Journal, 2025)
Manuscript type: Research Article Research Aims: to analyze the effect of donation collection method (allocation vs addition) and the level of materialism on attitude, total donation amount, program donation amount, and cost donation amount. Design/methodology/approach: This study used a between-subjects design with randomization. Data was collected through questionnaires administered to participants 18 years old and above, who are Indonesian citizens, resulting in 208 participants (102 participants in the Addition condition and 106 participants in the Allocation condition), and analyzed by ANCOVA. Research Findings: the result demonstrated only four hypotheses are supported that the significant role of the ADDITION donation collection method in shaping attitudes and increasing donation amount, in the form of intentions, and promoting higher donation behavior compared to ALLOCATION. Furthermore, materialism could enhance the donation amount only in ALLOCATION collection method. Theoretical Contribution/Originality: Using the Choice Architecture Theory, Framing Theory, and Nudging this study develop framework to strengthen the explanation of the effect of donation collection method on donation amount, and minimize cost donation aversion. Refer to Prospect Theory, framing of donation collection method shows how framing changes risk preferences. Practitioner/Policy Implication: If the foundation wants to collect donations for social activities that incur costs, the foundation can use a message design using the ADDITION method. This can increase positive responses in the form of a larger donation amount. Research limitation/Implications: This study employed a quasi-experimental online intervention that limited control over external variables, used a manual online randomization process, focused on post-intervention, did not conduct a baseline study, and was cross-sectional. Future studies should consider conducting a baseline study, longitudinal studies, and using a survey platform for randomization.